MULTIDIMENSIONAL PERSPECTIVES ON THE LEGAL SYSTEM AND JUSTICE ININDONESIA: A CRITICAL ANALYSIS OF THE INTERPLAY BETWEEN LEGAL NORMS,JUDICIAL PRACTICES, AND SOCIO-ECONOMIC FACTORS IN ACHIEVING SUBSTANTIVE JUSTICE - Susilowardani; Dara Pustika Sukma, Desi Syamsiah, Febri Atikawati Wiseno Putri, Asri Agustiwi (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This research delves into the multidimensional facets of the Indonesian legal system, employing a critical lens to dissect the intricate interplay between legal norms, judicial practices, and socio-economic factors in the pursuit of substantive justice. The study aims to unravel the complexities inherent in translating legal principles into practical application, scrutinizing the challenges within the judiciary that may impede the realization of justice. Furthermore, the research investigates the profound influence of socioeconomic factors on access to justice, shedding light on disparities that can significantly impact legal outcomes. By examining the dynamic intersectionality of legal norms, judicial practices, and socio-economic dynamics, this study contributes to a nuanced understanding of the Indonesian legal landscape. The findings of this research carry significant implications for the future trajectory of the legal system in Indonesia. Identifying challenges within the judiciary, such as systemic inefficiencies and regional variations, informs potential areas for reform. Moreover, exploring socio-economic factors underscores the need for targeted interventions to bridge gaps in legal representation and enhance the accessibility of justice. In conclusion, this study provides valuable insights into the multifaceted dimensions of the Indonesian legal system and lays the groundwork for recommendations to foster a more effective, transparent, and equitable legal environment.